Impact of Medicare Part D on Racial Disparities in Adherence to Cardiovascular Medications Among the Elderly. (August 2016) - Hussein, Mustafa; Waters, Teresa M.; Chang, Cyril F.; Bailey, James E.; Brown, Lawrence M.; Solomon, David K.
Medicare Part D improved medication adherence among the elderly, but to date, its effect on disparities in adherence remains unknown. We estimated Part D impact on racial/ethnic disparities in adherence to cardiovascular medications among seniors, using pooled data from the Medical Expenditure Panel Survey (2002-2010) on 14, 221 Medicare recipients (65+ years) and 3, 456 near-elderly controls (60-64 years). Study sample included White, Black, or Hispanic respondents who used at least one cardiovascular medication. Twelve-month adherence was measured as having an overall proportion of days covered ≥80%. Adherence disparities were defined according to the Institute of Medicine framework. Using difference-in-differences logistic regression, we found Part D to be associated with a 16-percentage-point decrease in the White–Hispanic disparity in overall adherence among seniors, net of the change among controls. Black–White disparities worsened only among men, by 21 percentage points. Increasing access and improving quality of medication use among disadvantaged seniors should remain a policy priority.